STUDI LITERATUR: EFEKTIVITAS METODE PROYEK DALAM MENINGKATKAN PERKEMBANGAN SOSIAL EMOSIONAL AUD - Nisna Nursarofah; Manda Nurhidayanti; Puput Patimah; Risbon Sianturi (LPPM Universitas Muhammadiyah Cirebon, 2023)
The golden age is the golden age in early childhood which at this time is the most appropriate period to stimulate various aspects of child development. Of the six aspects of development, one aspect that is important to be stimulated is the aspect of social emotional development. The social emotional aspect is known as an aspect that has an influence on a person's level of success. The higher the social emotional ability, the greater the probability of success. The method used in writing this article is a descriptive method using a qualitative research approach through literature study techniques. From the results of the review of several articles that are relevant to the title taken, the project method is effectively used by educators to stimulate children's social-emotional development. One of the effective learning methods used in PAUD is the project method which is a way to stimulate children's social emotional development. The advantage of this method is that children can be directly involved in a joint activity which will later trigger children to interact with their themes so that it affects their social development. The application of this project method can familiarize children to interact and socialize with their friends.